A LANDSLIDE SUSCEPTIBILITY ANALYSIS FOR BUZAU COUNTY, ROMANIA - VERONICA ZUMPANO; HAYDAR HUSSIN; PAOLA REICHENBACH; DAN BĂLTEANU; MIHAI MICU; SIMONE STERLACCHINI (Revue Roumaine de Géographie)
Landslides are one of the most common hazards in the Romanian Curvature Carpathians and Subcarpathians, covering a wide range of geomorphic mass wasting forms and processes. The purpose of this paper is to present a susceptibility analysis at regional scale for the Buzau County (Romania), focusing on shallow and medium-seated (sensu Bălteanu 1983) landslides. The susceptibility map was obtained using the weights-ofevidence modeling technique that allows understanding the significance of predisposing factors of shallow and medium-seated failures. The model was run considering eight environmental factors: slope, altitude, internal relief, planar and profile curvature, aspect, soil, land-use. A landslide inventory derived from archive data, literature review, field mapping and aerial imagery interpretation was divided into a training and a prediction set and was used to prepare and validate the model. The model performance was evaluated using the area under the ROC and the success rate curve. The susceptibility map represents an important step for landslide hazard and risk assessment, crucial components for the definition of adequate risk management strategies.